The Urgency of Islamic Law and Medical Considerations in Determining the Law on Female Circumcision - Moch. Afif Rif'an Hidayat; Aisyi Arsanitya; Fahmi Idris Assadi; Musrofaini Musrofaini; Salwa Zahra Ansori; M. Agus Budi Harto (International Tatho Academics, 2026)
This study aims to identify and explore the practice of female circumcision in Indonesia from the perspective of law and human rights, as well as the view of Islamic law according to Khalid Basalamah on female circumcision. This research uses a qualitative approach with primary data in the form of Khalied Basalamah's lecture content on female circumcision. Secondary data were obtained from various religious, medical, and human rights scientific literature to comprehensively examine the practice of female circumcision. The results of this study state that this study confirms that there are differences in views between culture, Islamic law, and global human rights principles. There is no strong Islamic legal basis to support the practice of female circumcision, which requires review in the current modern context. This study contributes to the importance of further research and in-depth contextual interviews on the impact of female” circumcision from a health perspective, both its positive and negative effects..